PKM kerajinan Inu dan kerupuk sagu Siberut Selatan Kabupaten Kepulauan Mentawai - Alfattory Rheza Syahrul; Kaksim Kaksim; Jimi Ronald (Unri Conference Series: Community Engagement, 2019)
Activity the PPM team provided training and mentoring to increase sales and production processes as well as the use of E Commerce application media as a medium for the right marketing for Melati 2 in Batjoja Village, Mentawai Island. The target of this activity is. 1) The business group gets knowledge and understanding of the basic concepts of sales. 2) Business groups have the knowledge and understanding of promotional media using E Commerce 3) Business groups can apply the knowledge gained from training with the right skills in managing production and promotion. The method in this activity is to analyze the situation of the community by giving several times of mentoring and training in the production process and sales promotion. The results obtained from this service activity are partners Very enthusiastic in activities and want to increase sales, but are still constrained by internet access. So that in online promotion is still constrained. While for sales directly experience an increase in orders.